Multiple anti-predator mechanisms in the red-spotted Argentina Frog (Amphibia: Hylidae) - Cajade, Rodrigo (2017)
Anurans employ a wide variety of anti-predator mechanisms to defend themselves. In casque-headed hylids, defence is thought to be a complex combination of several anti-predator mechanisms. However, the defence traits of only a few species are known; some hypotheses have yet to be addressed, whereas others, already tested in some species, need to be tested in additional taxa. The anti-predator mechanism of the casque-headed frog, Argenteohyla siemersi, is described here. It is a complex mechanism consisting of (1) behavioural and ecological traits, including secretive and semi-phragmotic habits and posture; (2) morphological features, including cryptic and aposematic colourations, a skull covered with bony dermal spines and protuberances that are associated with two types of granular venom glands; and (3) physiological and chemical traits, such as a highly lethal skin secretion. Our results are compared with those of previous studies of defence mechanisms in casque-headed frogs in an effort to understand the mechanisms and evaluate their potential phylogenetic signal in this group of anurans.